IMPLEMENTATION OF LIVESTOCK ANIMAL CONTROL POLICY IN LAPPA VILLAGE, SINJAI DISTRICT - A.M. Rizal Rinaldi Yusuf; Herlina Sakawati; Asri Nur Aina (Universitas Negeri Makassar, 2026)
The issue of stray livestock has become a significant concern in Lappa Village, Sinjai Regency. This phenomenon has caused various impacts, such as crop damage, traffic disruptions, and social conflicts within the community. This study aims to examine how the implementation of livestock management policies aligns with Van Meter and Van Horn's policy implementation theory. This theory highlights six key variables influencing the success of policy implementation: policy standards and objectives, resources, characteristics of implementing agencies, inter-organizational communication, implementers' disposition, and social, economic, and political environments. The research findings indicate that the implementation of livestock management policies in Lappa Village, Sinjai Regency, has been optimal. This conclusion is based on observations and interviews conducted during the study. However, some aspects still require attention and improvement. In terms of policy standards and objectives, they have been adequately met. However, some livestock owners in Lappa Village still fail to comply with Regional Regulation No. 4 of 2015 of Sinjai Regency. Regarding resources, the human resources for implementing the livestock control policy are sufficient, but financial resources remain inadequate, making the implementation process less effective. The characteristics of implementing agents have been effective, as the procedures are well-organized and executed according to standard operating procedures (SOPs). In the variables of social, economic, and political conditions, the lack of awareness among livestock owners regarding these regulations has led to many livestock still wandering in public facilities. The implementers’ attitude is both humane and firm in enforcing Regional Regulation No. 4 of 2015 of Sinjai Regency.